WHAT FACTORS INFLUENCE THE INTERNATIONALIZATION OF SMALL AND MEDIUM ENTERPRISES (SMES)? A GENDER-BASED APPROACH - Mulyanti, Rita Yuni; Wati, Lela Nurlaela; Suhana, Suhana (LPPM Universitas Jambi, 2025)
Small and medium enterprises (SMEs) are crucial to a nation's economy, especially in developing countries; nevertheless, their involvement in international trade, particularly exports, is minimal, with SMEs representing merely 15% of Indonesia's total non-oil and gas exports in 2024. Women manage Indonesian SMEs more than men, yet they encounter difficulties doing foreign activities. This study aims to analyze the elements influencing the internationalization of SMEs and gender-specific roles. The research sample consisted of 190 SMEs, with 137 operated by women and 53 by males. The data analysis employs moderating regression analysis (MRA) with Smart PLS. The study's findings reveal that the critical determinants for the internationalization of SMEs in Indonesia encompass entrepreneurial characteristics (age and experience), SME characteristics, entrepreneurial orientation, and environmental factors. A significant disparity exists between male-managed and female-managed SMEs concerning their characteristics, environmental factors, and regulatory structures. Female SMEs exhibit enhanced agility and compliance with regulations. The characteristics of SMEs and the environmental factors have a more significant impact on the internationalization of male SMEs than female SMEs. This study's novelty is in the elements that facilitate successful internationalization and the contribution of women-led SMEs to enhancing internationalization efforts. Although the study's sample included Indonesian SMEs, the findings may yield more significant implications for the success factors of SME internationalization worldwide concerning gender diversity. This study offers insights for policymakers to enhance SME internationalization by incorporating SMEs into extensive industrial ecosystems and fostering a collaborative environment among industry stakeholders and SMEs within the export product supply chain.